Respuesta :
Answer: The required solution is
[tex]y(t)=-\dfrac{7}{3}e^{-t}+\dfrac{7}{3}e^{\frac{1}{5}t}.[/tex]
Step-by-step explanation: We are given to solve the following differential equation :
[tex]5y^{\prime\prime}+3y^\prime-2y=0,~~~~~~~y(0)=0,~~y^\prime(0)=2.8~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
Let us consider that
[tex]y=e^{mt}[/tex] be an auxiliary solution of equation (i).
Then, we have
[tex]y^prime=me^{mt},~~~~~y^{\prime\prime}=m^2e^{mt}.[/tex]
Substituting these values in equation (i), we get
[tex]5m^2e^{mt}+3me^{mt}-2e^{mt}=0\\\\\Rightarrow (5m^2+3y-2)e^{mt}=0\\\\\Rightarrow 5m^2+3m-2=0~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~[\textup{since }e^{mt}\neq0]\\\\\Rightarrow 5m^2+5m-2m-2=0\\\\\Rightarrow 5m(m+1)-2(m+1)=0\\\\\Rightarrow (m+1)(5m-1)=0\\\\\Rightarrow m+1=0,~~~~~5m-1=0\\\\\Rightarrow m=-1,~\dfrac{1}{5}.[/tex]
So, the general solution of the given equation is
[tex]y(t)=Ae^{-t}+Be^{\frac{1}{5}t}.[/tex]
Differentiating with respect to t, we get
[tex]y^\prime(t)=-Ae^{-t}+\dfrac{B}{5}e^{\frac{1}{5}t}.[/tex]
According to the given conditions, we have
[tex]y(0)=0\\\\\Rightarrow A+B=0\\\\\Rightarrow B=-A~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(ii)[/tex]
and
[tex]y^\prime(0)=2.8\\\\\Rightarrow -A+\dfrac{B}{5}=2.8\\\\\Rightarrow -5A+B=14\\\\\Rightarrow -5A-A=14~~~~~~~~~~~~~~~~~~~~~~~~~~~[\textup{Uisng equation (ii)}]\\\\\Rightarrow -6A=14\\\\\Rightarrow A=-\dfrac{14}{6}\\\\\Rightarrow A=-\dfrac{7}{3}.[/tex]
From equation (ii), we get
[tex]B=\dfrac{7}{3}.[/tex]
Thus, the required solution is
[tex]y(t)=-\dfrac{7}{3}e^{-t}+\dfrac{7}{3}e^{\frac{1}{5}t}.[/tex]